Clinical InvestigationsNon isocentric film-based intracavitary brachytherapy planning in cervical cancer: a retrospective dosimetric analysis with CT planning - Tyagi, Kirti; Mukundan, Hari; Mukherjee, Deboleena; Semwal, Manoj; Sarin, Arti (Journal of Contemporary Brachytherapy, 2012)
Purpose : To compare intracavitary brachytherapy dose estimation for organs at risk (bladder and rectum) based on semi-orthogonal reconstruction of radiographs on non-isocentric X-ray unit and Computed Tomography (CT) – based volumetric planning in cervical cancer. Material and methods: Bladder and rectal points as per International Commission on Radiation Units and Measurements (ICRU) report 38, were retrospectively evaluated on 15 high dose rate intracavitary brachytherapy applications for cervical cancer cases. With the same source configuration as obtained during planning on radiographs performed on a non-isocentric X-ray unit, the mean doses to 2cc of most irradiated part of bladder and rectum were computed by CT planning and these estimates were compared with the doses at ICRU bladder and rectal points. Results: The mean ICRU point dose for bladder was 3.08 Gy (1.9-5.9 Gy) and mean dose to 2 cc (D2cc) bladder was 6.91 Gy (2.9-12.2 Gy). ICRU rectal dose was 3.8 Gy (2.4-4.45 Gy) and was comparable with D2cc rectum dose 4.2 Gy (2.8-5.9 Gy). Comparison of mean total dose (ICRU point vs. D2cc) for each patient was found to be significantly different for bladder (p = 0.000), but not for rectum (p = 0.08). Conclusions : On comparison of ICRU point based planning with volumetric planning on CT, it was found that bladder doses were underestimated by the film based method. However, the rectal doses were found to be similar to the D2cc doses. The results with non isocentric film based treatment planning were similar to the existing literature on orthogonal film based simulator planning.